HUBUNGAN TINGKAT PENGETAHUAN DENGAN PARTISIPASI PADA PEMERIKSAAN PAP SMEAR PADA WANITA PEKERJA SEKS KOMERSIAL - Kurniawan, Bayu; Asmika, Asmika; Sarwono, Imam (Jurnal Kedokteran Brawijaya, 2008)
ABSTRACT Carcinoma cervix is the most frequent malignancy and the highest cancer mortality rate in women worldwideas well as in Indonesian. From 4.290 of cervical carciona in Indonesia , 1.326 cases were found in SurabayaOver 70% patients were in the advanced stadium. Pap Smear as a screening test is a prevention strategy focarcinoma  cervix.  Sex  worker    has  a  high  risk  for  carcinoma  cervix.  This  research  was  carried  out  in  GangDolly  Prostitution  Area  Surabaya  aimed  to  describe  the  characteristics  of  sex  worker  and  the  correlationbetween    knowledge  level  and  participation  in  Pap  Smear  examination  .  A  cross  sectional  approach  wasconducted with  67 respondents. The variables: characteristics, knowledge  level and pap-smear  participationwas  measured  by  open  and  close-ended  questionnaire  guided  by  the  researcher.  The  data  were  presentedas  cross  tabulation  and  further  testing  the  correlation  based  on    Lambda  Correlation  test  (α  =  0,05).  Theresults  showed    an  equal  proportion  of  good  and  sufficient  knowledge  and  only  limited  respondent  (2,99%who  have  very  poor  knowledge.  89,55%  respondents  have  had  done  their  Pap  Smear  examination,  fromthose  mostly  were  respondents  with  sufficient  knowledge  (41,79%).    There  was  a  weak  and  not  significancorrelation  between  respondent’s  knowledge  level  about  carcinoma  cervix  and  their  participation  in  PapSmear examination (Lambda Correlation test, Lb = 0,286, approx. sig. = 0,151).  Keywords : Knowledge , Carcinoma Cervix, Pap Smear, Participation